Stress fracture of the femoral neck after the Pipkin type IV hip injury - Gvozdenović, Nemanja; Ninković, Srdjan; Jovanović, Mladen; Marić, Dušica (Vojnosanitetski pregled, 2021)
Introduction. Hip fractures/dislocations of Pipkin type IV are rare, often accompanied by complications and poor outcome. We describe a complication in the form of a stress fracture of the femoral neck (SFOFN) after the Pipkin type IV fracture – dislocation of the hip. Case report. A healthy male, TAXI driver, aged 60, was injured in a traffic accident and admitted as a polytraumatised patient with the Pipkin type IV hip injury. Open reduction and internal fixation had been done. Completely recovered, 9 months after the injury during a walk he felt pain in the operated hip and was unable to bear weight. We noted a dislocated subcapital SFOFN which did not form on the site of the previous osteosynthesis. Conclusion. Pipkin type IV hip injury as a result of polytrauma, unstable joint and osteosynthesis, inadequate weight bearning and disposal of physical therapy, increases the risk of complications such as avascular necrosis, or as in our case, a stress fracture (caused by weight overload).
Keywords: hip dislocation; hip fracture; multiple trauma; fractures, stress; orthopedics; reoperation.